2020
DOI: 10.24953/turkjped.2020.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Infection risk after paediatric liver transplantation

Abstract: Infections after liver transplantation (LT), despite prophylactic therapy, are still important causes of morbidity and mortality in children. Although underlying disease and immunosuppression along with the complexity of LT procedure are the major predispositions to infections, there still might be under recognised factors predisposing infections in paediatric LT. In this study, we retrospectively analysed the risk factors of bacterial, viral, and fungal infections after LT in a series of 167 children (median … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Despite the advancements in surgical techniques, immunosuppressive therapies, and improved post-operative care, bacterial infections remain the most important complication amongst paediatric liver transplant recipients (LTR) [1][2][3][4][5][6]. The overall incidence of bacterial infections varies from centre to centre, with studies reporting an incidence of 25 to 68% [1][2][3][4]7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advancements in surgical techniques, immunosuppressive therapies, and improved post-operative care, bacterial infections remain the most important complication amongst paediatric liver transplant recipients (LTR) [1][2][3][4][5][6]. The overall incidence of bacterial infections varies from centre to centre, with studies reporting an incidence of 25 to 68% [1][2][3][4]7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In some centres, infections are the most common cause of mortality after LT. Underlying disease, malnutrition, immunosuppression and complexity of LT procedure are the major predispositions to infections [9]. The infection rate in our centre was as high as 68% and it was the main cause of mortality.…”
Section: Discussionmentioning
confidence: 74%
“…Studies have shown up to 80% of patients experience at least one infection episode within the first year of LT [9]. And some reported the rate of infection following liver transplantation is between 47% and 80%, with a mean of one to 2.5 episodes of infections per patient [8].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study from our center showed higher percentages of CMV infection (60%) for pediatric LTR on long term follow up, up to 2 years [ 5 ]. In contrast, a Turkish study reported low incidence of CMV (23.4%) and EBV (15.6%) infection, likely due to less frequent monitoring of CMV and EBV DNA [ 15 ]. It is noticeable that viral infections in adults post-LT does not impose a major burden, as it does in the pediatric population.…”
Section: Discussionmentioning
confidence: 99%